2019
DOI: 10.1136/bmjopen-2019-031365
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosed prevalence of Ehlers-Danlos syndrome and hypermobility spectrum disorder in Wales, UK: a national electronic cohort study and case–control comparison

Abstract: ObjectivesTo describe the epidemiology of diagnosed hypermobility spectrum disorder (HSD) and Ehlers-Danlos syndromes (EDS) using linked electronic medical records. To examine whether these conditions remain rare and primarily affect the musculoskeletal system.DesignNationwide linked electronic cohort and nested case–control study.SettingRoutinely collected data from primary care and hospital admissions in Wales, UK.ParticipantsPeople within the primary care or hospital data systems with a coded diagnosis of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 41 publications
4
146
0
3
Order By: Relevance
“…Hypermobile EDS is the most common type of EDS and is thought to account for 80–90% of EDS cases (Tinkle et al, ). The incidence of hEDS is not currently known but a recent study suggests a combined incidence of hEDS and hypermobility spectrum disorders (HSD) at 10 in 5000 (Demmler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypermobile EDS is the most common type of EDS and is thought to account for 80–90% of EDS cases (Tinkle et al, ). The incidence of hEDS is not currently known but a recent study suggests a combined incidence of hEDS and hypermobility spectrum disorders (HSD) at 10 in 5000 (Demmler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…90 Demmler et al recently reported the combined prevalence of hEDS and HSD to be 1 in 500 people in Wales with 70% of the diagnosed being women, suggesting that hEDS/HSD prevalence has been grossly underestimated. 91 With the spectrum of severity, variation in symptom presentation and the lack of an effective clinical diagnostic test, it is not uncommon for patients to go years undiagnosed with hEDS. Because of this, it can be assumed that the actual prevalence of hEDS is higher than reported.…”
Section: Epidemiologymentioning
confidence: 99%
“…T A B L E 3 The five-point questionnaire 91 1. Can you now (or could you ever) place your hands flat on the floor without bending your knees?…”
Section: Gynecological Manifestationsmentioning
confidence: 99%
“…21.20025072 doi: medRxiv preprint relationships. A rich debate has been stimulated by a recent paper reporting the prevalence of EDS and JHS 33 . While other forms of EDS are likely rare, the present study suggests hEDS is common among patients with pain and fatigue.…”
Section: Beighton Scorementioning
confidence: 99%